Education Strategic Planning: Manpower Planning Approach Study - Fuad Rinaldi; Suryana Sumantri; Muchtarom Muchtarom; Erry Hndriawan; Firman Firman (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the importance of educational strategic planning due to curriculum changes. This study aims to describe the strategic planning of education. The research method used is descriptive with a qualitative approach. Using observation data collection techniques, documentation, and open interviews in a semi-structured manner. The results of this study explain that educational planning can be obtained from understanding the nature of educational planning itself by teachers and all stakeholders. Understanding of educational planning is also obtained from socialization and training on the latest educational discoveries or advances that can allow schools to adapt to the needs and developments of the times in accordance with educational laws and the school's vision and mission. Educational planning is also obtained from the willingness of the leadership and all stakeholders in preparing educational strategic planning and carrying out several approaches, one of which is the manpower planning approach. The employment approach or the Manpower Planning Approach is very suitable for use in Vocational High Schools because the employment approach will focus on the link and match of school graduates. So that stakeholders, especially school principals, teachers and parents of students participate in helping to increase the competitiveness of graduates.